2003
DOI: 10.1046/j.1432-1033.2003.03566.x
|View full text |Cite
|
Sign up to set email alerts
|

Open questions in ferredoxin‐NADP+ reductase catalytic mechanism

Abstract: Ferredoxin (flavodoxin)-NADP(H) reductases (FNR) are ubiquitous flavoenzymes that deliver NADPH or low potential one-electron donors (ferredoxin, flavodoxin) to redox-based metabolisms in plastids, mitochondria and bacteria. The plant-type reductase is also the basic prototype for one of the major families of flavin-containing electron transferases that display common functional and structural properties. Many aspects of FNR biochemistry have been extensively characterized in recent years using a combination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
297
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 250 publications
(314 citation statements)
references
References 83 publications
17
297
0
Order By: Relevance
“…The higher dynamic motion in the NADP ϩ -flexible subdomain at pD r 8.0 than at pD r 6.0 is most likely to facilitate rapid sampling in the conformational space for selecting the most suitable conformation for enhancing the binding affinity for NADP ϩ , especially in the first binding step of the adenosine portion of NADP ϩ in the bipartite NADP ϩ binding mode (20,35). The fact that the presence of NADP ϩ at the active site is a prerequisite for the catalysis of FNR (35) can explain why the NADP ϩ -flexible subdomain exhibits the higher motional behavior than other regions of FNR at pD r 8.0.…”
Section: Discussionmentioning
confidence: 99%
“…The higher dynamic motion in the NADP ϩ -flexible subdomain at pD r 8.0 than at pD r 6.0 is most likely to facilitate rapid sampling in the conformational space for selecting the most suitable conformation for enhancing the binding affinity for NADP ϩ , especially in the first binding step of the adenosine portion of NADP ϩ in the bipartite NADP ϩ binding mode (20,35). The fact that the presence of NADP ϩ at the active site is a prerequisite for the catalysis of FNR (35) can explain why the NADP ϩ -flexible subdomain exhibits the higher motional behavior than other regions of FNR at pD r 8.0.…”
Section: Discussionmentioning
confidence: 99%
“…The net CO 2 uptake rate at saturating CO 2 internal concentration (A max ) and the initial slope at low Ci were derived from Ci response curves by fitting experimental data to the equation of a nonrectangular hyperbola as described (Hajirezaei et al, 2002). reaction (Bruns and Karplus, 1995;Carrillo and Ceccarelli, 2003). Whereas many functional properties of FNR have been thoroughly characterized (Carrillo and Ceccarelli, 2003;Ceccarelli et al, 2004), until recently, little was known on the actual contribution of this flavoenzyme to electron transport and photosynthesis in planta.…”
Section: Discussionmentioning
confidence: 99%
“…reaction (Bruns and Karplus, 1995;Carrillo and Ceccarelli, 2003). Whereas many functional properties of FNR have been thoroughly characterized (Carrillo and Ceccarelli, 2003;Ceccarelli et al, 2004), until recently, little was known on the actual contribution of this flavoenzyme to electron transport and photosynthesis in planta. The combined use of FNR antisense (Hajirezaei et al, 2002) and overexpressing transgenic plants (this work) revealed somehow paradoxical behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 In the SpnQ case, a similar electron relay path as in the E 1 -E 3 reaction may be operative (see Scheme 2, path A). It should be noted that when E 1 was assayed in the presence of its natural substrate (10), ferredoxin/ferredoxin reductase, and NADPH, it was five-fold less effective at C-3 deoxygenation than when assayed using E 3 under standard conditions (18% versus 100% conversion after 1.5 h at 25 °C).…”
mentioning
confidence: 99%